"One‐pot" synthesis of crosslinked silicone‐containing macromolecular charring agent and its synergistic flame retardant poly(l‐lactic acid) with ammonium polyphosphate. (6th February 2017) - Guan, Yanyan; Wen, Xin; Yang, Hongfan; Zhang, Lipeng; Li, Mingang; Shao, Jing; Li, Yunhui; Tang, Tao
Abstract : A crosslinked silicone‐containing macromolecular charring agent (CSi‐MCA) was synthesized via "one‐pot" process, and it was combined with ammonium polyphosphate (APP) to synergistically improve the flame retardancy of poly(l ‐lactic acid) (PLA). The chemical structure of synthesized CSi‐MCA was characterized by Fourier transform infrared spectroscopy and solid‐state 13 C nuclear magnetic resonance. The thermal gravimetric analyzer indicated that the CSi‐MCA displayed good thermal stability and high residue via the catalytic crosslinking. Furthermore, the flame retardant effect of CSi‐MCA and APP as intumescent flame retardants in PLA system was investigated by limited oxygen index, UL94, and cone calorimeter test. When the content of CSi‐MCA was 5 wt% and APP was 10 wt% (CSi‐MCA/APP = 1/2), the limited oxygen index value of composites was 33.6 and UL94 classed a V‐0 rating. The peak heat release rate and total heat release of PLA composites containing both APP and CSi‐MCA decreased significantly in comparison with those with APP or CSi‐MCA alone. The flame retardancy mechanism was investigated via analyzing residual chars by scanning electron microscopy and X‐ray photoelectron spectroscopy as well as the possible chemical reaction between APP and CSi‐MCA by thermal gravimetric analyzer and Fourier transform infrared spectroscopy. The results showed that the enhanced flame retardancy was attributed mainly to synergistic effect of CSi‐MCA and APP, which could form a compact, continuous, and protective layer during combustion. Copyright © 2017 John Wiley & Sons, Ltd.